Perbedaan Keterampilan Komunikasi Antara Mahasiswa Preklinik Dan Klinik Fakultas Kedokteran Universitas Lampung - Devi Mutiara Jasmine; Oktafany; Dwita Oktaria (Medula, 2019)
Communication is needed in daily life because communication is important. Communicating means conveying messages from the giver of the message to one or more recipients of the message with or without using a tool. The communicating component is a giver, message, recipient, and media. Communication skills in medical education are taught from the academic stage to the profession stage. Learning effective communication at the academic stage is applied to the tutorial and Clinical Skill Lab (CSL) with simulated patients. While at the profession stage, young doctors have carried out effective communication learning that is directly applied to patients and their families in real terms. This study used a cross sectional design with 66 respondents selected using proportional stratified sampling techniques. The research data was taken from filling out the Interpersonal Communication Competence Scale questionnaire that was developed by Rubin and Martin assessed with 10 indicators of ICCS. Data were analyzed using T test. A total of 66 respondents filled out a questionnaire and the results showed that there were differences in communication skills between preclinical students and clinical at the Faculty of Medicine, University of Lampung with a value of p = 0.002. Thus, the communication skills of preclinical students are lower than those of clinical students with the result of the mean difference being 0.515. There were differences in communication skills between preclinical students and clinical at the Faculty of Medicine, University of Lampung.